The lock-up phenomenon of exhaled flow in a stable thermally-stratified indoor environment. (1st May 2017) - Zhou, Qi; Qian, Hua; Ren, Haigang; Li, Yuguo; Nielsen, Peter V.
Abstract: Expiratory flows of an infected individual can spread diseases in indoor environment. This probably explains why there have been many studies of how exhaled flow disperses and interacts with ventilation. A number of experimental studies have found that the exhaled flows can be locked up in the stratified layer in a room ventilated by displacement; however, its mechanism has not been explored so far. A non-dimensional theoretical buoyant jet dispersion model was developed here to compare the dispersion characteristics of the exhaled flow in a thermally stratified environment with those in a thermally uniform environment. Our results show that the exhaled flow can freely float upward in a uniform environment while it exhibits an oscillatory trajectory at a certain height in a thermally stratified environment. The terminal temperature of exhaled jet flow is equal to the ambient temperature. The latter is the so-called lock-up phenomenon as observed in some early studies. In displacement ventilation, the location of the lock-up layer is lower than the stratification height. A smaller Ar number and a steeper temperature gradient lead to a lower lock-up height in a thermally stratified environment. The variation of the lock-up height with different temperature gradients is found to follow a power law relation. Highlights: The lock-up phenomenon in thermally-stratified environment is explained using jet mechanics. Non-dimensional governing equations of buoyant jet are derived. The lock-up height of exhaled flow can be predicted by using a simple buoyant jet model. A smaller Ar number or a steeper temperature gradient leads to a lower lock-up height. Variation of lock-up height in different temperature gradients follows a power law relation.